Joining technology and biology to solve conservation problems through translocation in the endangered limpet Patella ferruginea - Espinosa, Free; Maestre, Manuel; García-Gómez, José Carlos; Cotaina-Castro, María Isabel; Pitarch-Moreno, Carmen; Paramio, Juan Manuel; Fort-Santa María, Patricia; García-Estévez, Natalia (Frontiers in Marine Science, 2023)
The Anthropocene era is characterized by a biodiversity crisis, where many species are pushing to extinction, causing alteration of the stability in the ecosystems and loss of their services. In this context, the translocation of endangered species is a powerful resource in conservation as long as its goals and appropriateness are clearly stated and it matches unambiguous criteria. Patella ferruginea is one of the most endangered marine species in the Mediterranean, and several translocations have been made with limited results in terms of survival. A methodology that mimics the natural topography of the substrate in the donor population based on Artificial Inert Mobile Substrates (AIMS, 40x20x10 cm) is proposed for restocking purposes. Three different treatments were tested: on substrate, slope, and cantilever depending on the position in which the AIMS were deployed. A total of 660 AIMS were installed within the donor area. The installation of such AIMS did not negatively affect either donor or receiving populations. A total of 188 specimens were translocated in three different attempts in 2018, 2019, and 2020, and no mortality was observed during the translocation process that lasted 24 h. Survival through the medium and long-term for the translocated specimens ranged from 80.6 to 91.5% after one month, 55.5 to 80.9% after eight months, and 48.4 to 76.6% after one year, with survival in the control population being 91.6% after four months and 87.5% after one year. Overall, recruits showed higher survival values than adults, whereas substrate treatment hosted more specimens (both recruits and adults) than slope and cantilever ones, while recruits were more abundant on cantilever treatment. The methodology has been proven to be useful for restocking and reintroduction purposes between donor and receiving areas.